Avaliação da qualidade da água residuária da aquaponia para fins de irrigação no semiárido brasileiro - Medeiros, Letícia Gabriela Saraiva Silva de (Universidade Federal Rural do Semi-Árido, 2019)
The Brazilian semiarid is characterized as a strategic area for sustainable management, as it is a region that presents problems of water scarcity and activities potentially producing degradation of water quality. The disposal of aquaponics wastewater in the soil has advantages such as waste treatment, water supply and nutrient availability to plants. However, because these effluents are abundant in nutrients, soil disposal without proper management can impact the soil-plant systems. The present work aimed to characterize and analyze the aquaponics effluent in relation to the risks of salinization, sodification and plant toxicity. Six weekly collections were performed in the aquaponics system of the Aquaculture Sector on Universidade Federal Rural do Semi-Árido, East Campus, Mossoró-RN to determine the values of pH, temperature, sodium, electrical conductivity, calcium, magnesium, potassium, carbonate, bicarbonate and chloride. The aquaponics system was supplied with two types of water: a) well water and b) public water supply. The values of the physicochemical attributes of aquaponics wastewater samples were submitted to descriptive statistical analysis to determine maximum and minimum values, mean, median, standard deviation and coefficient of variation. The results indicate that aquaponics wastewater from public water supply may be a viable alternative for more efficient use of water in agricultural production processes; and aquaponics wastewater obtained from well water did not meet most standards for irrigation use, so it was not recommended for this use without the adoption of special water and soil management practices.
Monografia
Keywords: Salinidade; Toxicidade; Irrigação; Íons; Salinity; Toxicity; Irrigation; Ions; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA